DEVELOPMENT OF A MINIATURIZED VERSION OF DICENTRIC CHROMOSOME ASSAY TOOL FOR RADIOLOGICAL TRIAGE. Issue 1 (21st September 2018) - Balajee, Adayabalam S; Smith, Tammy; Ryan, Terri; Escalona, Maria; Dainiak, Nicholas
Abstract: Use of ionizing radiation (IR) in various industrial, medical and other applications can potentially increase the risk of medical, occupational or accidental human exposure. Additionally, in the event of a radiological or nuclear (R/N) incident, several tens of hundreds and thousands of people are likely to be exposed to IR. IR causes serious health effects including mortality from acute radiation syndrome and therefore it is imperative to determine the absorbed radiation dose, which will enable physicians in making an appropriate clinical 'life-saving' decision. The 'Dicentric Chromosome Assay (DCA)' is the gold standard for estimating the absorbed radiation dose but its performance is time consuming and laborious. Further, timely evaluation of dicentric chromosomes (DCs) for dose estimation in a large number of samples provides a bottleneck because of a limited number of trained personnel and a prolonged time for manual analysis. To circumvent some of these technical issues, we developed and optimized a miniaturized high throughput version of DCA (mini-DCA) in a 96-microtube matrix with bar-coded 1.4 ml tubes to enable the processing of a large number of samples. To increase the speed of DC analysis for radiation dose estimation, a semi-automated scoring was optimized using the Metafer DCScore algorithm. The accuracy of mini-DCA in dose estimation was verified and validated though comparison with conventional DCA performed in 15 ml conical tubes. The mini-DCA considerably reduced the sample processing time by a factor of 4 when compared to the conventional DCA. Further, the radiation doses estimated by mini-DCA using the triage mode of scoring (50 cells or 30 DCs) were similar to that of conventional DCA using 300–500 cells. The mini-DCA coupled with semi-automated DC scoring not only reduced the sample processing and analysis times by a factor of 4 but also enabled the processing of a large number of samples at once. Our mini-DCA method, once automated for high throughput robotic platforms, will be an effective radiological triage tool for mass casualty incidents.